2021
DOI: 10.1073/pnas.2102902118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of peptide: N -glycanase causes proteasome dysfunction mediated by a sugar-recognizing ubiquitin ligase

Abstract: Mutations in the human peptide:N-glycanase gene (NGLY1), which encodes a cytosolic de–N-glycosylating enzyme, cause a congenital autosomal recessive disorder. In rodents, the loss of Ngly1 results in severe developmental delay or lethality, but the underlying mechanism remains unknown. In this study, we found that deletion of Fbxo6 (also known as Fbs2), which encodes a ubiquitin ligase subunit that recognizes glycoproteins, rescued the lethality-related defects in Ngly1-KO mice. In NGLY1-KO cells, FBS2 overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…A recent report by Yoshida and colleagues showed that simultaneous knockout of a sugar-recognizing F-box protein (FBS2; official name: FBXO6) rescued the lethality and motor functions in Ngly1 knockout mice [ 79 ], suggesting that FBS2 makes a major contribution to Ngly1 loss-of-function phenotypes. FBS2 and its homolog, FBS1, are cytosolic components of ERAD that recognize high-mannose glycans—usually found on misfolded N -glycoproteins—and promote the ubiquitination of such proteins, as well as their proteasomal degradation [ 80 , 81 ].…”
Section: Ngly1 and The Erad Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report by Yoshida and colleagues showed that simultaneous knockout of a sugar-recognizing F-box protein (FBS2; official name: FBXO6) rescued the lethality and motor functions in Ngly1 knockout mice [ 79 ], suggesting that FBS2 makes a major contribution to Ngly1 loss-of-function phenotypes. FBS2 and its homolog, FBS1, are cytosolic components of ERAD that recognize high-mannose glycans—usually found on misfolded N -glycoproteins—and promote the ubiquitination of such proteins, as well as their proteasomal degradation [ 80 , 81 ].…”
Section: Ngly1 and The Erad Pathwaymentioning
confidence: 99%
“…Because the glycan structure recognized by FBS2 is removed from the N -glycoproteins by NGLY1, loss of NGLY1 is predicted to generate new targets for FBS2 binding and their subsequent ubiquitination. Accordingly, Yoshida et al used “nuclear factor erythroid 2-like 1” (NFE2L1; also called NRF1), as a well-known ERAD substrate and one of the direct targets of NGLY1 (see below), to examine this notion [ 79 ]. They showed that in the absence of NGLY1, the SFC FBS2 ubiquitin ligase ubiquitinates NFE2L1 and inhibits its nuclear transport.…”
Section: Ngly1 and The Erad Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpressed FOXB6 not only induced ubiquitination of NFE2L1, but also inhibited the processing by DDI2 and nuclear localization in cells without NGLY1. Interestingly, addition knockout of Foxb6 could make Ngly1-deficient mice (Foxb6 −/− ;Ngly1 −/− ) viable and exhibiting normal motor functions [103]. The survival ratio at P0 was 2 times higher than in Engase; Ngly1 dKO mice [101].…”
Section: Inhibition Foxb6 (Fbs2)mentioning
confidence: 99%
“…SKN‐1A, which is the NRF1 ortholog in C aenorhabditis elegans , has four functionally important N ‐glycosylated Asn residues and genetic studies have elegantly shown that the conversion of all of these residues to Asp by PNG‐1, which is the NGLY1 ortholog in C. elegans , is required to maintain the expression of proteasome subunit genes [62]. Human NRF1 contains nine N ‐glycosylation sites in the large luminal domain [63] that consists of a transactivation domain and a DNA‐binding domain [64], which is constitutively dislocated into the cytosol, deglycosylated by NGLY1, and degraded by proteasomes. However, an insufficiency of or the inhibition of proteasomes prevents the proteasomal degradation of NRF1, and this allows the proteolytic activation of deglycosylated NRF1 by an aspartyl protease, the DNA‐damage inducible 1 homologue 2 [60].…”
Section: The Biosynthesis and Degradation Of Glycoproteinsmentioning
confidence: 99%